An insight into esthetical appreciation of natural lyric. From impressionistic randomness towards (contemporary) environmental laments - Stanek, Libor (Bohemica Olomucensia, 2020)
The aim of this thesis is not to provide a complete list of every poetic movement which was interested in nature as such. However, the text is focusing on several selected impressionistic and environmental poetry collections through which the thesis will demonstrate different examples how a poet can deal with natural lyric. The list of chosen poems should outline concrete groups of metaphors which are characteristic for poetic movements aforementioned.
Keywords: Natural poetry; aesthetic appreciation of nature; contemporary Czech poetry; impressionism; environmental poetry